Kedudukan Outsourcing Pasca Putusan Mahkamah Konstitusi nomor 27/PUU-IX/2011 - Khairani Khairani (The Constitutional Court of the Republic of Indonesia, 2014)
The presence of the labor law is often challenged by the supporters of the interests primarily of the workers, particularly with regard to setting Outsourcing Employment Agreement in Indonesia. The reason the opponents are, among others, that the outsourcing arrangement only exploit and marginalize the humanity of those who have been guaranteed by the constitution. Various attempts have them do to rule as discriminatory was removed from employment practices in Indonesia, including the choice of law rules of the test material to the Constitutional Court. Finally, through Decision of The Constitutional Court No. 27/PUU-IX/2011, the Court granted the petition of workers by declaring unconstitutional some provisions of the Employment Agreement Outsourcing. In addressing the decision of the Court, the Government through the Ministry of Manpower publishes Permenakertrans No. 19, 2012. The problem is that the Constitutional Court’s decision should not be followed up with legislation level ministerial regulations. In addition, it violates the rules Permenakertrans the higher, the Manpower Act for doing addition and subtraction of the torso aforementioned law. Not only that, now, both the workers and the employers also feel is not in line with the employment agreement outsourcing arrangement within the meaning of the Permenakertrans.